Accuracy test of the Kato-Katz and direct examination method for diagnosing helminthiasis using preserved stool - Gunasari, Lala Foresta Valentine; Triana, Dessy; Suringgar, Sadid Reyudo (BKM Public Health and Community Medicine, 2022)
Purposes: More than 1.5 billion people, or a quarter of the world's popula-:on, are infected by soil-transmi>ed helminth (STH). Children aged 2-14 years are the most suscep:ble to helminthiasis. In Indonesia, there are 60.4 million children infected with STH, with an average prevalence rate of 31.8%. Helminthiasis can cause growth and development disorders in children. The diagnosis of helminthiasis can be made by examining stool using qualitative (direct examination) and quantitative (Kato-Katz) methods. This study aimed to determine the accuracy of both methods in diagnosing helminthiasis using preserved stool specimens. Methods: This research design was an observational study with a cross-sec-:onal approach. A total of 140 stool samples preserved using 10% formalin for 13 months were examined with the Kato-Katz and direct examination methods using a light microscope. Results: Among the 140 stool samples examined, 64 samples (45.71%) were found positive for STH using the Kato-Katz method, while with the direct examination method, 50 samples (35.71%) were positive for STH. The accuracy test showed that the sensitivity and specificity values of the Kato Katz method were 86.79% and 79.31%, while the direct examination method was 64.15% and 81.60%, respectively. Conclusions: The Kato-Katz method was more sensitive than the direct examination method in diagnosing helminthiasis in preserved stool, but the direct examination method had a higher specificity value than the Kato-Katz method. In addition, the accuracy of examination of fresh and preserved stool specimens in diagnosing helminthiasis was not significantly different.